Inequalities for eigenvalues of a system of higher-order differential equations - Sun, H.J. (Український математичний журнал, 2014)
We establish some sharper inequalities for eigenvalues of a system of higher-order differential equations. Moreover, we present some sharper estimates for the upper bound of the (k +1)th eigenvalue and the gaps of its consecutive eigenvalues. Встановлено дєякі 6ільш точні оцінки для власних значень системи диференціальних рівнянь вищого порядку. Ми також наводимо деякі більш точні оцінки для оцінки зверху (k +1)-го власного значення i щілин між будь-якими двома послідовними власними значеннями.